2013
DOI: 10.1038/sc.2013.75
|View full text |Cite
|
Sign up to set email alerts
|

Training effectiveness when teaching the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) to medical students

Abstract: Study design: Interventional training sessions. Objectives: To examine the effectiveness of training medical students in the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). Setting: A Peking University teaching hospital. Methods: A total of 46 medical students were involved in the study. First, they had a 2-h self-study session with the ISNCSCI booklet, followed by a 10-item questionnaire. The booklet was allowed for use as a reference during this assessment. Two days l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…This kind of analysis was previously performed exclusively in the artificial setting of ISNCSCI instructional courses. 7,[10][11][12][13][14][15][16][17][18][19][20][21] In the framework of instructional courses, the effects of a formal ISNCSCI training are typically assessed by the same test before (pre-test) and after the training (post-test). In both tests, the attendees rate and classify a predefined set of ISNCSCI cases.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of analysis was previously performed exclusively in the artificial setting of ISNCSCI instructional courses. 7,[10][11][12][13][14][15][16][17][18][19][20][21] In the framework of instructional courses, the effects of a formal ISNCSCI training are typically assessed by the same test before (pre-test) and after the training (post-test). In both tests, the attendees rate and classify a predefined set of ISNCSCI cases.…”
Section: Discussionmentioning
confidence: 99%
“…AIS classification performances above 90% still seem to be hard to achieve. Liu et al postulated 15 that NLI classification performance does not need be evaluated, because the NLI can be deduced from SLs and MLs. However, we found approximately 9% misclassified NLIs, revealing that the NLI is actually the third most error-prone ISNCSCI variable after ML and AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the inter-rater and intra-rater reliability of ISNCSCI [15][16][17][18][19][20][21][22][23][24][25][26]. Generally, intra-rater and inter-rater agreements among trained or experienced raters were acceptable; [17,[21][22][23] however, even for trained examiners, the agreements of sensory and/or motor examination were less reliable in patients with an incomplete SCI than in those with a complete SCI [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…In order to accurately assess AIS, it is mandatory to determine the sensory level, sensory scores, motor level and strength of the key muscles using the ISNCSCI classification [14]. The ISNCSCI method was tested for its inter-and intra-rater reliabilities [15][16][17][18][19][20][21][22][23][24][25][26]. This method is slightly complicated, and several studies illustrated that training and experience may be required for accurate agreement [15,20,21,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation